Health-related quality of life in hemoglobinopathies: A systematic review from a global perspective - Rodigari, Francesca; Brugnera, Giorgia; Colombatti, Raffaella (Frontiers in Pediatrics, 2022)
Background: Sickle cell disease (SCD) and thalassemia are inherited blood disorders, which can lead to life-threatening events and chronic organ damage. Recent advances in treatments have increased the life expectancy of patients and hemoglobinopathies have become chronic illnesses with social and emotional impairments. Thus, health related quality of life (HRQOL) assessment has a fundamental role in disease management and treatment: generic and disease-specific questionnaires are reliable and validated measures to estimate disease burden. The heterogeneous distribution of treatment opportunities worldwide influences physical, social and emotional disease perception. Objectives: To review publications concerning HRQOL for SCD and thalassemia in different areas of the world in order to gather a global perspective of questionnaires used and outcomes evaluated. Methods: We conducted systematic searches of keyword combinations in PubMed. Our research included Clinical Trial, Meta-Analysis, Randomized Controlled Trial, Reviews and Systematic Reviews from 2000 to 2021. Results: 124 articles from Pubmed were included in our study. HRQOL evaluation is conducted in all continents but with less frequency in Europe for SCD and in South East Asia and Africa for thalassemia. Generic HRQOL questionnaires (PROMIS, SF-36, PedsQL) are frequently adopted while disease-specific ones (ASCQMe, SCSES for SCD, TranQoL for thalassemia) are less used. Translation into local languages has been often performed. Conclusions: HRQOL is a complex outcome that has been increasingly incorporated in clinical research and clinical practice worldwide, although with regional differences. Disease specific outcomes (pain for SCD, transfusion burden for thalassemia) as well as health care system characteristics, especially in low-income countries, have an impact on HRQOL and should be considered in healthcare plans. Keywords: sickle cell disease, thalassemia, hemoglobinopathies, health related quality of life, PROMIS, SF-36, PedsQL-SCD, Peds- QOL, Tran-QoL, SCSES, ASCQ-Me.